Assessment of knowledge and indicators of drinking water, sanitation, and hygiene practices from rural and urban schools of Belagavi, Karnataka: a cross-sectional study - Sarawade, Ravindra; Reddy, Chelikam Veeraraghavendra; Patil, Darshan; Revagoud, Kalmeshwar (International Journal Of Community Medicine And Public Health, 2026)
Background: Adequate water, sanitation, and hygiene (WASH) in schools is essential for preventing communicable diseases and promoting health. However, gaps often persist between students’ knowledge and the availability of WASH infrastructure. This study aimed to assess WASH-related knowledge among school children and to evaluate school-level WASH indicators in rural and urban schools of Belagavi district, Karnataka. Methods: A cross-sectional study was conducted from March 2023 to May 2024 among 422 students from grades VI-VIII across 40 schools (25 rural, 15 urban). Students’ WASH knowledge was assessed using a pre-tested questionnaire, while school WASH indicators were evaluated using standardised facility assessment tools. Data were analysed using descriptive statistics and chi-square tests. Results: Overall, 51.2% of students demonstrated good WASH knowledge. Awareness that unsafe water affects health was reported by 68.2%, and 99.5% recognised the disease risk of not washing hands. All schools had drinking water and handwashing facilities; however, consistent year-round water availability was reported by only 50% of rural and 37.5% of urban schools. Soap was absent at handwashing points in over 90% of schools. Rural schools more frequently had pit latrines and fewer usable toilets, while toilet cleanliness was reported in 55% of rural and 37.5% of urban schools. Conclusions: Moderate WASH knowledge among students coexists with substantial infrastructural gaps, particularly the lack of soap, inadequate sanitation facilities, and inconsistent water availability. Strengthening school WASH infrastructure and maintenance is critical to translate knowledge into effective hygiene practices.